Data Presentation in Qualitative Research: The Outcomes of the Pattern of Ideas with the Raw Data - Aisha Ibrahim Ningi (International Journal of Qualitative Research, 2022)
The data presentation is one of the segments of the methodology in every research depending on the approach. The methodology, therefore, refers to the design and the theory that underpins the research. The paper contained a detailed explanation of the steps taken from the researcher’s interactions with the raw data and how such data was presented or analyzed. The data processing used observations, interviews, and audio recordings to have a balanced presentation. The pattern of ideas in data presentation involved familiarizing with the data to generate initial codes, searching for themes, defining and producing the report. Thus, the paper gives the reader a clear view of how qualitative data are presented and discussed with credibility. It is recommended that a researcher must rely on a wide range of sources of data that would help to produce an in-depth and holistic portrait of the participants' experiences.